2023
DOI: 10.1186/s12889-023-15962-8
|View full text |Cite
|
Sign up to set email alerts
|

Predicting self-perceived general health status using machine learning: an external exposome study

Abstract: Background Self-perceived general health (SPGH) is a general health indicator commonly used in epidemiological research and is associated with a wide range of exposures from different domains. However, most studies on SPGH only investigated a limited set of exposures and did not take the entire external exposome into account. We aimed to develop predictive models for SPGH based on exposome datasets using machine learning techniques and identify the most important predictors of poor SPGH status.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Furthermore, previous studies have shown that general health reflects not only physical health but also mental health (Bezuidenhout et al, 2023), because general health is a broader outcome than physical and mental health (Shi et al, 2022). A wide range of factors are known to be associated with health status (Hoekstra et al, 2023), such as lifestyle (Isola, 2020), socioeconomic status (Nadi et al, 2020), wellbeing at work (de Ceballos and Santos, 2015), anxiety (Malakoutikhah et al, 2022), perceived disease burden (Nielsen et al, 2015), sociodemographic factors (Tinella et al, 2022), work facilitation (Shi et al, 2022), and work ability (Kisiel et al, 2023). By conducting a thorough review, studies show other multidimensional models, however, it is believed that for this non-clinical study it is better suited using the GHQ-12 (Montazeri et al, 2003;Hystad and Johnsen, 2020;Mayhew et al, 2021;Lütke et al, 2022).…”
Section: General Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that general health reflects not only physical health but also mental health (Bezuidenhout et al, 2023), because general health is a broader outcome than physical and mental health (Shi et al, 2022). A wide range of factors are known to be associated with health status (Hoekstra et al, 2023), such as lifestyle (Isola, 2020), socioeconomic status (Nadi et al, 2020), wellbeing at work (de Ceballos and Santos, 2015), anxiety (Malakoutikhah et al, 2022), perceived disease burden (Nielsen et al, 2015), sociodemographic factors (Tinella et al, 2022), work facilitation (Shi et al, 2022), and work ability (Kisiel et al, 2023). By conducting a thorough review, studies show other multidimensional models, however, it is believed that for this non-clinical study it is better suited using the GHQ-12 (Montazeri et al, 2003;Hystad and Johnsen, 2020;Mayhew et al, 2021;Lütke et al, 2022).…”
Section: General Healthmentioning
confidence: 99%
“…And in this context, general health has an important meaning in the lives of workers in the education sector, where this construct has currently been linked to many others: such as coping strategies (Tinella et al, 2022), depression (Gladstone et al, 2018), job insecurity (Setati et al, 2015), psychological discomfort (Jakubiec et al, 2014), machine learning (Hoekstra et al, 2023), working capacity (Kisiel et al, 2023), quality of life (Bezuidenhout et al, 2023), among other. Understanding general health as the mental, emotional and physical wellbeing that allows us to face challenges (Lunde et al, 2022) and acquire greater concentration in the activities that are carried out (Chavez-Espinoza et al, 2022).…”
Section: Introductionmentioning
confidence: 99%